Jump to navigation Jump to search

General

Display information for equation id:math.7085.3 on revision:7085

* Page found: Lagrange reversion theorem (eq math.7085.3)

(force rerendering)

Occurrences on the following pages:

Hash: 95778f490efea11c573a9dc683f540a0

TeX (original user input):

 g(v) = \int \delta(y f(z) - z + x) g(z) (1-y f'(z)) \, dz

TeX (checked):

g(v)=\int \delta (yf(z)-z+x)g(z)(1-yf'(z))\,dz

LaTeXML (experimental; uses MathML) rendering

MathML (8.705 KB / 1.354 KB) :

g ( v ) = δ ( y f ( z ) - z + x ) g ( z ) ( 1 - y f ( z ) ) 𝑑 z 𝑔 𝑣 𝛿 𝑦 𝑓 𝑧 𝑧 𝑥 𝑔 𝑧 1 𝑦 superscript 𝑓 𝑧 differential-d 𝑧 {\displaystyle g(v)=\int\delta(yf(z)-z+x)g(z)(1-yf^{\prime}(z))\,dz}
<math xmlns="http://www.w3.org/1998/Math/MathML" id="p1.1.m1.1" class="ltx_Math" alttext="{\displaystyle g(v)=\int\delta(yf(z)-z+x)g(z)(1-yf^{\prime}(z))\,dz}" display="inline">
  <semantics id="p1.1.m1.1a">
    <mrow id="p1.1.m1.1.36" xref="p1.1.m1.1.36.cmml">
      <mrow id="p1.1.m1.1.36.1" xref="p1.1.m1.1.36.1.cmml">
        <mi id="p1.1.m1.1.1" xref="p1.1.m1.1.1.cmml">g</mi>
        <mo id="p1.1.m1.1.36.1.1" xref="p1.1.m1.1.36.1.1.cmml"></mo>
        <mrow id="p1.1.m1.1.36.1.2" xref="p1.1.m1.1.36.1.cmml">
          <mo stretchy="false" id="p1.1.m1.1.2" xref="p1.1.m1.1.36.1.cmml">(</mo>
          <mi id="p1.1.m1.1.3" xref="p1.1.m1.1.3.cmml">v</mi>
          <mo stretchy="false" id="p1.1.m1.1.4" xref="p1.1.m1.1.36.1.cmml">)</mo>
        </mrow>
      </mrow>
      <mo id="p1.1.m1.1.5" xref="p1.1.m1.1.5.cmml">=</mo>
      <mstyle displaystyle="true" id="p1.1.m1.1.36.2" xref="p1.1.m1.1.36.2.cmml">
        <mrow id="p1.1.m1.1.36.2a" xref="p1.1.m1.1.36.2.cmml">
          <mo largeop="true" symmetric="true" id="p1.1.m1.1.6" xref="p1.1.m1.1.6.cmml"></mo>
          <mrow id="p1.1.m1.1.36.2.1" xref="p1.1.m1.1.36.2.1.cmml">
            <mi id="p1.1.m1.1.7" xref="p1.1.m1.1.7.cmml">δ</mi>
            <mo id="p1.1.m1.1.36.2.1.1" xref="p1.1.m1.1.36.2.1.1.cmml"></mo>
            <mrow id="p1.1.m1.1.36.2.1.2" xref="p1.1.m1.1.36.2.1.2.2.cmml">
              <mo stretchy="false" id="p1.1.m1.1.8" xref="p1.1.m1.1.36.2.1.2.2.cmml">(</mo>
              <mrow id="p1.1.m1.1.36.2.1.2.2" xref="p1.1.m1.1.36.2.1.2.2.cmml">
                <mrow id="p1.1.m1.1.36.2.1.2.2.1" xref="p1.1.m1.1.36.2.1.2.2.1.cmml">
                  <mrow id="p1.1.m1.1.36.2.1.2.2.1.1" xref="p1.1.m1.1.36.2.1.2.2.1.1.cmml">
                    <mi id="p1.1.m1.1.9" xref="p1.1.m1.1.9.cmml">y</mi>
                    <mo id="p1.1.m1.1.36.2.1.2.2.1.1.1" xref="p1.1.m1.1.36.2.1.2.2.1.1.1.cmml"></mo>
                    <mi id="p1.1.m1.1.10" xref="p1.1.m1.1.10.cmml">f</mi>
                    <mo id="p1.1.m1.1.36.2.1.2.2.1.1.1a" xref="p1.1.m1.1.36.2.1.2.2.1.1.1.cmml"></mo>
                    <mrow id="p1.1.m1.1.36.2.1.2.2.1.1.2" xref="p1.1.m1.1.36.2.1.2.2.1.1.cmml">
                      <mo stretchy="false" id="p1.1.m1.1.11" xref="p1.1.m1.1.36.2.1.2.2.1.1.cmml">(</mo>
                      <mi id="p1.1.m1.1.12" xref="p1.1.m1.1.12.cmml">z</mi>
                      <mo stretchy="false" id="p1.1.m1.1.13" xref="p1.1.m1.1.36.2.1.2.2.1.1.cmml">)</mo>
                    </mrow>
                  </mrow>
                  <mo id="p1.1.m1.1.14" xref="p1.1.m1.1.14.cmml">-</mo>
                  <mi id="p1.1.m1.1.15" xref="p1.1.m1.1.15.cmml">z</mi>
                </mrow>
                <mo id="p1.1.m1.1.16" xref="p1.1.m1.1.16.cmml">+</mo>
                <mi id="p1.1.m1.1.17" xref="p1.1.m1.1.17.cmml">x</mi>
              </mrow>
              <mo stretchy="false" id="p1.1.m1.1.18" xref="p1.1.m1.1.36.2.1.2.2.cmml">)</mo>
            </mrow>
            <mo id="p1.1.m1.1.36.2.1.1a" xref="p1.1.m1.1.36.2.1.1.cmml"></mo>
            <mi id="p1.1.m1.1.19" xref="p1.1.m1.1.19.cmml">g</mi>
            <mo id="p1.1.m1.1.36.2.1.1b" xref="p1.1.m1.1.36.2.1.1.cmml"></mo>
            <mrow id="p1.1.m1.1.36.2.1.3" xref="p1.1.m1.1.36.2.1.cmml">
              <mo stretchy="false" id="p1.1.m1.1.20" xref="p1.1.m1.1.36.2.1.cmml">(</mo>
              <mi id="p1.1.m1.1.21" xref="p1.1.m1.1.21.cmml">z</mi>
              <mo stretchy="false" id="p1.1.m1.1.22" xref="p1.1.m1.1.36.2.1.cmml">)</mo>
            </mrow>
            <mo id="p1.1.m1.1.36.2.1.1c" xref="p1.1.m1.1.36.2.1.1.cmml"></mo>
            <mrow id="p1.1.m1.1.36.2.1.4" xref="p1.1.m1.1.36.2.1.4.2.cmml">
              <mo stretchy="false" id="p1.1.m1.1.23" xref="p1.1.m1.1.36.2.1.4.2.cmml">(</mo>
              <mrow id="p1.1.m1.1.36.2.1.4.2" xref="p1.1.m1.1.36.2.1.4.2.cmml">
                <mn id="p1.1.m1.1.24" xref="p1.1.m1.1.24.cmml">1</mn>
                <mo id="p1.1.m1.1.25" xref="p1.1.m1.1.25.cmml">-</mo>
                <mrow id="p1.1.m1.1.36.2.1.4.2.1" xref="p1.1.m1.1.36.2.1.4.2.1.cmml">
                  <mi id="p1.1.m1.1.26" xref="p1.1.m1.1.26.cmml">y</mi>
                  <mo id="p1.1.m1.1.36.2.1.4.2.1.1" xref="p1.1.m1.1.36.2.1.4.2.1.1.cmml"></mo>
                  <msup id="p1.1.m1.1.36.2.1.4.2.1.2" xref="p1.1.m1.1.36.2.1.4.2.1.2.cmml">
                    <mi id="p1.1.m1.1.27" xref="p1.1.m1.1.27.cmml">f</mi>
                    <mo id="p1.1.m1.1.28.1" xref="p1.1.m1.1.28.1.cmml"></mo>
                  </msup>
                  <mo id="p1.1.m1.1.36.2.1.4.2.1.1a" xref="p1.1.m1.1.36.2.1.4.2.1.1.cmml"></mo>
                  <mrow id="p1.1.m1.1.36.2.1.4.2.1.3" xref="p1.1.m1.1.36.2.1.4.2.1.cmml">
                    <mo stretchy="false" id="p1.1.m1.1.29" xref="p1.1.m1.1.36.2.1.4.2.1.cmml">(</mo>
                    <mi id="p1.1.m1.1.30" xref="p1.1.m1.1.30.cmml">z</mi>
                    <mo stretchy="false" id="p1.1.m1.1.31" xref="p1.1.m1.1.36.2.1.4.2.1.cmml">)</mo>
                  </mrow>
                </mrow>
              </mrow>
              <mo rspace="4.2pt" stretchy="false" id="p1.1.m1.1.32" xref="p1.1.m1.1.36.2.1.4.2.cmml">)</mo>
            </mrow>
            <mo id="p1.1.m1.1.36.2.1.1d" xref="p1.1.m1.1.36.2.1.1.cmml"></mo>
            <mrow id="p1.1.m1.1.36.2.1.5" xref="p1.1.m1.1.36.2.1.5.cmml">
              <mo rspace="0pt" id="p1.1.m1.1.34" xref="p1.1.m1.1.34.cmml">𝑑</mo>
              <mi id="p1.1.m1.1.35" xref="p1.1.m1.1.35.cmml">z</mi>
            </mrow>
          </mrow>
        </mrow>
      </mstyle>
    </mrow>
    <annotation-xml encoding="MathML-Content" id="p1.1.m1.1b">
      <apply id="p1.1.m1.1.36.cmml" xref="p1.1.m1.1.36">
        <eq id="p1.1.m1.1.5.cmml" xref="p1.1.m1.1.5"/>
        <apply id="p1.1.m1.1.36.1.cmml" xref="p1.1.m1.1.36.1">
          <times id="p1.1.m1.1.36.1.1.cmml" xref="p1.1.m1.1.36.1.1"/>
          <ci id="p1.1.m1.1.1.cmml" xref="p1.1.m1.1.1">𝑔</ci>
          <ci id="p1.1.m1.1.3.cmml" xref="p1.1.m1.1.3">𝑣</ci>
        </apply>
        <apply id="p1.1.m1.1.36.2.cmml" xref="p1.1.m1.1.36.2">
          <int id="p1.1.m1.1.6.cmml" xref="p1.1.m1.1.6"/>
          <apply id="p1.1.m1.1.36.2.1.cmml" xref="p1.1.m1.1.36.2.1">
            <times id="p1.1.m1.1.36.2.1.1.cmml" xref="p1.1.m1.1.36.2.1.1"/>
            <ci id="p1.1.m1.1.7.cmml" xref="p1.1.m1.1.7">𝛿</ci>
            <apply id="p1.1.m1.1.36.2.1.2.2.cmml" xref="p1.1.m1.1.36.2.1.2">
              <plus id="p1.1.m1.1.16.cmml" xref="p1.1.m1.1.16"/>
              <apply id="p1.1.m1.1.36.2.1.2.2.1.cmml" xref="p1.1.m1.1.36.2.1.2.2.1">
                <minus id="p1.1.m1.1.14.cmml" xref="p1.1.m1.1.14"/>
                <apply id="p1.1.m1.1.36.2.1.2.2.1.1.cmml" xref="p1.1.m1.1.36.2.1.2.2.1.1">
                  <times id="p1.1.m1.1.36.2.1.2.2.1.1.1.cmml" xref="p1.1.m1.1.36.2.1.2.2.1.1.1"/>
                  <ci id="p1.1.m1.1.9.cmml" xref="p1.1.m1.1.9">𝑦</ci>
                  <ci id="p1.1.m1.1.10.cmml" xref="p1.1.m1.1.10">𝑓</ci>
                  <ci id="p1.1.m1.1.12.cmml" xref="p1.1.m1.1.12">𝑧</ci>
                </apply>
                <ci id="p1.1.m1.1.15.cmml" xref="p1.1.m1.1.15">𝑧</ci>
              </apply>
              <ci id="p1.1.m1.1.17.cmml" xref="p1.1.m1.1.17">𝑥</ci>
            </apply>
            <ci id="p1.1.m1.1.19.cmml" xref="p1.1.m1.1.19">𝑔</ci>
            <ci id="p1.1.m1.1.21.cmml" xref="p1.1.m1.1.21">𝑧</ci>
            <apply id="p1.1.m1.1.36.2.1.4.2.cmml" xref="p1.1.m1.1.36.2.1.4">
              <minus id="p1.1.m1.1.25.cmml" xref="p1.1.m1.1.25"/>
              <cn type="integer" id="p1.1.m1.1.24.cmml" xref="p1.1.m1.1.24">1</cn>
              <apply id="p1.1.m1.1.36.2.1.4.2.1.cmml" xref="p1.1.m1.1.36.2.1.4.2.1">
                <times id="p1.1.m1.1.36.2.1.4.2.1.1.cmml" xref="p1.1.m1.1.36.2.1.4.2.1.1"/>
                <ci id="p1.1.m1.1.26.cmml" xref="p1.1.m1.1.26">𝑦</ci>
                <apply id="p1.1.m1.1.36.2.1.4.2.1.2.cmml" xref="p1.1.m1.1.36.2.1.4.2.1.2">
                  <csymbol cd="ambiguous" id="p1.1.m1.1.36.2.1.4.2.1.2.1.cmml" xref="p1.1.m1.1.36.2.1.4.2.1.2">superscript</csymbol>
                  <ci id="p1.1.m1.1.27.cmml" xref="p1.1.m1.1.27">𝑓</ci>
                  <ci id="p1.1.m1.1.28.1.cmml" xref="p1.1.m1.1.28.1"></ci>
                </apply>
                <ci id="p1.1.m1.1.30.cmml" xref="p1.1.m1.1.30">𝑧</ci>
              </apply>
            </apply>
            <apply id="p1.1.m1.1.36.2.1.5.cmml" xref="p1.1.m1.1.36.2.1.5">
              <csymbol cd="latexml" id="p1.1.m1.1.34.cmml" xref="p1.1.m1.1.34">differential-d</csymbol>
              <ci id="p1.1.m1.1.35.cmml" xref="p1.1.m1.1.35">𝑧</ci>
            </apply>
          </apply>
        </apply>
      </apply>
    </annotation-xml>
    <annotation encoding="application/x-tex" id="p1.1.m1.1c">{\displaystyle g(v)=\int\delta(yf(z)-z+x)g(z)(1-yf^{\prime}(z))\,dz}</annotation>
  </semantics>
</math>

SVG (13.931 KB / 4.473 KB) :

g times left-parenthesis v right-parenthesis equals integral delta times left-parenthesis y times f times left-parenthesis z right-parenthesis minus z plus x right-parenthesis times g times left-parenthesis z right-parenthesis times left-parenthesis 1 minus y times f prime times left-parenthesis z right-parenthesis right-parenthesis times italic d z

SVG with PNG fallback (MathML can be enabled via browser plugin) rendering

MathML (1.385 KB / 440 B) :

g ( v ) = δ ( y f ( z ) z + x ) g ( z ) ( 1 y f ( z ) ) d z {\displaystyle g(v)=\int \delta (yf(z)-z+x)g(z)(1-yf'(z))\,dz}
<math xmlns="http://www.w3.org/1998/Math/MathML" display="block" alttext="{\displaystyle g(v)=\int \delta (yf(z)-z+x)g(z)(1-yf'(z))\,dz}">
  <semantics>
    <mrow class="MJX-TeXAtom-ORD">
      <mstyle displaystyle="true" scriptlevel="0">
        <mi>g</mi>
        <mo stretchy="false">(</mo>
        <mi>v</mi>
        <mo stretchy="false">)</mo>
        <mo>=</mo>
        <mo>&#x222B;<!-- ∫ --></mo>
        <mi>&#x03B4;<!-- δ --></mi>
        <mo stretchy="false">(</mo>
        <mi>y</mi>
        <mi>f</mi>
        <mo stretchy="false">(</mo>
        <mi>z</mi>
        <mo stretchy="false">)</mo>
        <mo>&#x2212;<!-- − --></mo>
        <mi>z</mi>
        <mo>+</mo>
        <mi>x</mi>
        <mo stretchy="false">)</mo>
        <mi>g</mi>
        <mo stretchy="false">(</mo>
        <mi>z</mi>
        <mo stretchy="false">)</mo>
        <mo stretchy="false">(</mo>
        <mn>1</mn>
        <mo>&#x2212;<!-- − --></mo>
        <mi>y</mi>
        <msup>
          <mi>f</mi>
          <mo>&#x2032;</mo>
        </msup>
        <mo stretchy="false">(</mo>
        <mi>z</mi>
        <mo stretchy="false">)</mo>
        <mo stretchy="false">)</mo>
        <mspace width="thinmathspace" />
        <mi>d</mi>
        <mi>z</mi>
      </mstyle>
    </mrow>
    <annotation encoding="application/x-tex">{\displaystyle g(v)=\int \delta (yf(z)-z+x)g(z)(1-yf'(z))\,dz}</annotation>
  </semantics>
</math>

SVG (9.728 KB / 4.009 KB) :

{\displaystyle g(v)=\int \delta (yf(z)-z+x)g(z)(1-yf'(z))\,dz}

Translations to Computer Algebra Systems

Translation to Maple

In Maple:

Translation to Mathematica

In Mathematica:

Similar pages

Calculated based on the variables occurring on the entire Lagrange reversion theorem page

Identifiers

MathML observations

0results

0results

no statistics present please run the maintenance script ExtractFeatures.php

0 results

0 results